Anemia In Toddlers Of Kattankulathur, Kancheepuram District, (Tamil Nadu) India - B. SUDHAGANDHI,; A. PREMA,; S. SUNDARESAN,; W. EBENEZER WILLIAM,; G.SHIVASHEKAR, (International Journal of Pharma and Bio Sciences, 2012)
The aim of this study was to assess the prevalence of anemia and its relation to variables such as age, gender, weight, height, mother’s education, total family numbers, Birth order, number of children in the family and socio economic factor in toddlers of Kattankulathur area.A cross-sectional investigation using both qualitative and quantitative methods was adopted for data collection. Hemoglobin levels of toddlers were estimated by cyanmethemoglobin method. A toddler with hemoglobin less than 11 g/dL was considered as anemic. Chi-square test was used to assess the relationship of anemia with its variables. Information regarding birth order of child, number of siblings, total family members and mothers’ education was obtained. Height and weight were measured.Investigation is based around the rural area of SRM hospital, Kattankulathur.Toddlers aged 1 to 3 years.The prevalence of anemia was reported 75.2 %. The percentage of anemic children among male and female was deducted 79.1% and 71.7 % respectively. BMI, total family members, mothers’ education and socio economic factor were important determinants of anemia. There was no significant relationship between anemia and birth order of child and number of siblings.The prevalence of anemia in toddlers was high 75.2 %. All the malnourished toddlers should be propro screened for anemia.